Smear slide microscopy images of IODP Hole 386-M0086B - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Collection of smear slide microscopy images from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan. This was followed by an onshore phase onboard D/V Chikyu between 2022-02-14 – 2022-03-15. During the offshore phase, smear slides were prepared from paleontology samples collected with a tip-cut syringe from section ends every 5 m. During the onshore phase, smear slides samples were collected every 2 m to complement visual core description observations and identify the composition of fine-grained sediment. The smear slides were prepared by putting a small amount of sediment on a glass slide mixed with distilled water. The slide was subsequently evaporated on a hot plate, and the dried sample was mounted in Norland Optical Adhesive 61 using ultraviolet light. Sediment grain size and composition were examined under a polarized light petrographic microscope (Zeiss Axio Imager A1m POL-1) with an ocular micrometer. With a few exceptions, one photo with open and one with crossed nicol prisms was taken of each slide. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023